Privatizing Roads : A New Method for Auctioning Highways - Engel, Eduardo; Fischer, Ronald; Galetovic, Alexander (World Bank, Washington, DC, 2012)
The authors attribute many of the problems in highway privatization to the combined effect of features of the highway business and the fixed term contracts used. First, traffic forecasts are notoriously imprecise, and the franchise holder has almost no control over demand. Second, most franchises have been awarded for a fixed term that is independent of demand realization. They propose a new mechanism the --least-present-value-of-revenue auction-- that overcomes flaws in the fixed term franchise because the contract term automatically adjusts to traffic growth. If traffic grows more slowly than expected, the term lengthens and if more rapidly, it shortens. The basic principle underlying the auction is that the franchise holder should not make losses when the long-run demand for the highway is sufficient to pay all costs.